2010
DOI: 10.1111/j.1472-765x.2010.02947.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of real-time PCR for quantification of Legionella spp. in spa water

Abstract: Aims:  Legionella bacteria ubiquitously colonize natural freshwater and are responsible for legionellosis in humans. Several cases of legionellosis have been associated in particular with the use of whirlpool spas. The objective of this study was to verify whether real‐time PCR is applicable for the quantification of Legionella spp. in spa water. Methods and Results:  The study compared concentrations obtained by real‐time PCR vs that obtained by conventional culture for 101 spa water samples. For the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
(49 reference statements)
2
12
0
Order By: Relevance
“…All building owners were informed about the visit. Water samples from cooling towers located near outbreak cases were cultured (131 cooling tower samples from 70 buildings) according to a standardized AFNOR NF T90-431 method as described above [39]. Colonies growing only on BCYE agar were considered as Legionella spp.…”
Section: Methodsmentioning
confidence: 99%
“…All building owners were informed about the visit. Water samples from cooling towers located near outbreak cases were cultured (131 cooling tower samples from 70 buildings) according to a standardized AFNOR NF T90-431 method as described above [39]. Colonies growing only on BCYE agar were considered as Legionella spp.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidenced in environmental studies that detected a higher level of bacterial DNA than was corroborated by culture and where the persistence of Legionella DNA after multiple rounds of remediation resulted in no detectable culture growth (183,338,341,342,384). As a consequence, PCR has a low positive predictive value (PPV) for legionellae compared to that of culture methods in environmental settings; conversely, PCR has a high negative predictive value for viable Legionella in the same samples (Ն97%) (341,343). Interestingly, PCR in clinical applications may have a higher PPV (than for environmental samples) despite the lower sensitivity with nonrespiratory specimens (379).…”
Section: Nucleic Acid-based Molecular Diagnosticsmentioning
confidence: 97%
“…Since the mainstream introduction of real-time PCR, numerous groups have evaluated the efficacy of nucleic acid detection alongside culture and other established methods. Assuming proper bioinformatics and primer/probe design and stringency, most NAAT-based assays are highly specific (close to 100%), and the growing consensus is that the sensitivity of PCR (both conventional and real time) is equal to or greater than that of culture-based detection using specimens from the lower respiratory tract or environmental water samples (286,(335)(336)(337)(338)(339)(340)(341)(342)(343)(344). Notably, the success of both PCR and culture for LD diagnosis is positively correlated with disease severity.…”
Section: Nucleic Acid-based Molecular Diagnosticsmentioning
confidence: 99%
“…in spa water, the real-time PCR data was compared with traditional culture based measurements (Guillemet et al 2010). The results showed that using the Water Environment Research, Volume 83, Number 10-Copyright © 2011 Water Environment Federation culture method, Legionella was detected in 14 out of 101 samples with concentrations ranging from 250 to 3.5 x 10 5 colony forming units (CFU) per liter.…”
Section: Polymerase Chain Reaction Assays Formentioning
confidence: 99%